PREVENTING SUICIDAL BEHAVIOR IN ADOLESCENTS - Mammadzada, Mahammad (Health and Society, 2025)
The factors related to social, psychological, environment that lead to suicidal behaviors are discussed in this article. This work illustrates how the risk factors such as depression, social isolation, family conflicts, and lack of public support result in suicide. This article also highlights how school-based psychological programs, societal support, and strong family relationships play a key role in preventing suicidal behavior. The article especially emphasizes that high-risk groups—such as LGBTQ youth, adolescents from low-income families, and those exposed to violence require more targeted intervention. Additionally, using three standardized tests, adolescents’ levels of depression and hope for the future were measured through the administration of the DASS and CHS. Furthermore, the Reasons for Living (RFL) scale was used to identify the underlying motivations that prevent suicidal behavior.